Desenvolvimento de dobras e falhas em ambiente distensional: aplicação da modelagem física - Gaspar, Diogo Fonseca Alves (2010)
The geological modeling allows, at laboratory scaling, the simulation of the geometric and kinematic evolution of geological structures. The importance of the knowledge of these structures grows when we consider their role in the creation of traps or conduits to oil and water. In the present work we simulated the formation of folds and faults in extensional environment, through physical and numerical modeling, using a sandbox apparatus and MOVE2010 software. The physical modeling of structures developed in the hangingwall of a listric fault, showed the formation of active and inactive axial zones. In consonance with the literature, we verified the formation of a rollover between these two axial zones. The crestal collapse of the anticline formed grabens, limited by secondary faults, perpendicular to the extension, with a curvilinear aspect. Adjacent to these faults we registered the formation of transversal folds, parallel to the extension, characterized by a syncline in the fault hangingwall. We also observed drag folds near the faults surfaces, these faults are parallel to the fault surface and presented an anticline in the footwall and a syncline hangingwall. To observe the influence of geometrical variations (dip and width) in the flat of a flat-ramp fault, we made two experimental series, being the first with the flat varying in dip and width and the second maintaining the flat variation in width but horizontal. These experiments developed secondary faults, perpendicular to the extension, that were grouped in three sets: i) antithetic faults with a curvilinear geometry and synthetic faults, with a more rectilinear geometry, both nucleated in the base of sedimentary pile. The normal antithetic faults can rotate, during the extension, presenting a pseudo-inverse kinematics. ii) Faults nucleated at the top of the sedimentary pile. The propagation of these faults is made through coalescence of segments, originating, sometimes, the formation of relay ramps. iii) Reverse faults, are nucleated in the flat-ramp interface. Comparing the two models we verified that the dip of the flat favors a differentiated nucleation of the faults at the two extremities of the mater fault. V These two flat-ramp models also generated an anticline-syncline pair, drag and transversal folds. The anticline was formed above the flat being sub-parallel to the master fault plane, while the syncline was formed in more distal areas of the fault. Due the geometrical variation of these two folds we can define three structural domains. Using the physical experiments as a template, we also made numerical modeling experiments, with flat-ramp faults presenting variation in the flat. Secondary antithetic, synthetic and reverse faults were generated in both models. The numerical modeling formed two folds, and anticline above the flat and a syncline further away of the master fault. The geometric variation of these two folds allowed the definition of three structural domains parallel to the extension. These data reinforce the physical models. The comparisons between natural data of a flat-ramp fault in the Potiguar basin with the data of physical and numerical simulations, showed that, in both cases, the variation of the geometry of the flat produces, variation in the hangingwall geometry